MODAL BUDAYA SEBAGAI PENGUAT PEMBENTUKAN KARAKTER BERBASIS AJARAN KI HADJAR DEWANTARA DI SEKOLAH DASAR - Heri Maria Zulfiati; Suyanto Suyanto; Hadjar Pamadhi (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2019)
This study aims to describe the formation of characters through the strengthening of Ki Hadjar Dewantara's cultural capital based teachings. The research setting was Taman Muda Ibu Pawiyatan elementary school in Yogyakarta City, Indonesia and it is one of the schools established by Ki Hadjar Dewantara, the Indonesian educational leader and hero. This qualitative research was designed as a case study using the purposive sampling with individual resources such as headmaster, teacher, student representatives, school committee, parents, foundation management and school supervisor. The data analysis deals with an interactive model of Miles and Huberman.. To test the data validity, researchers used theÂ  triangulation technique and reference materials. The research results show that the implementation of cultural capital in terms of character education at SD Taman Muda Ibu Pawiyatan deals with methods of habituation, examples and exemplaries integrated with learning, extracurricular and daily activities at home and in society